Draught animal power network [1] - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
The International Livestock Centre for Africa (ILCA) is currently putting together a list of people, institutions and organizations working on draught animal power in Africa in order to establish a network of those concerned. This would enable...